Attention regulates anger and fear to predict changes in adolescent risk‐taking behaviors. (3rd October 2014) - Kim‐Spoon, Jungmeen; Holmes, Christopher; Deater‐Deckard, Kirby
Abstract : Background: Regulation of negative affect is critical to healthy development in childhood and adolescence. We conducted a longitudinal study examining the moderating role of attention control in the effects of anger and fear on changes in risk‐taking behaviors from early to middle adolescence. Method: The sample involved participants from the Study of Early Child Care and Youth Development (SECCYD), assessed at 9, 11, and 15 years of age. Composite scores for anger, fear, and attention control were computed using indicators from multiple informants, and risk‐taking behaviors were assessed based on adolescents' self‐reports. Results: Latent difference score analysis indicated significant moderating effects of attention control showing that increased anger between 9 and 11 years was related to increases in risk‐taking behaviors between 11 and 15 years only for adolescents with low attention control but not for adolescents with high attention control. In contrast, significant moderating effects of attention control for the link between fear and risk‐taking behaviors suggested increased fear between 9 and 11 years tended to be associated with decreases in risk‐taking behaviors between 11 and 15 years only for adolescents with high attention control, but not for adolescents with low attention control. Conclusions: Attention control regulates the connections between negative affect such as anger and fear with changes in adolescent risk‐taking behaviors. Our data suggest the protective role of strong attention control against the development of risk‐taking behaviors in adolescence as it demotes the effects of anger and promotes the effects of fear.